"After thirty falls" : new essays on John Berryman - Coleman, Philip; McGowan, Philip, 1969- (DQR studies in literature ;, 2007)
Prefaced by an account of the early days of Berryman studies by bibliographer and scholar Richard J. Kelly, " After thirty Falls " is the first collection of essays to be published on the American poet John Berryman (1914-1972) in over a decade. The book seeks to provoke new interest in this important figure with a group of original essays and appraisals by scholars from Ireland, the United Kingdom, Hong Kong, and the United States. Exploring such areas as the poet's engagements with Shakespeare and the American sonnet tradition, his use of the Trickster figure and the idea of performance in h